Les jeunes et Wikipédia : un rapport genré ? - Gilles Sahut (Revue de recherches en littératie médiatique multimodale, 2016)
Les jeunes ont fréquemment recours à Wikipédia, mais la confiance qu’ils accordent à cette encyclopédie collaborative n’est pas optimale et sa réputation demeure controversée. Les filles/femmes font-elles preuve d’une plus grande défiance vis-à-vis de cette source si particulière ? D’après le modèle de sélectivité, elles seraient plus sensibles aux risques informationnels et plus prudentes dans leur démarche évaluative. L’enquête par questionnaire menée auprès de 841 jeunes âgés de 11 à 25 ans montre l’existence de différences genrées à propos de la confiance épistémique en Wikipédia, de la sensibilité à sa réputation et des connaissances informationnelles à son sujet. Néanmoins, la prise en compte du niveau de scolarité amène à nuancer l’influence du genre sur le rapport à cette source.
Keywords: confiance épistémique; culture informationnelle; genre; jeunesse; Wikipédia

JAMES- Jeunes, activités, médias - enquête Suisse - Willemsee, I.; Waller, G.; Genner, S. Suter; Oppliger, S.; Huber, A.; Suss, D. (Haute École des sciences appliquées., 2014)
Depuis 2010, plus de 1000 adolescents âgés de 12 à 19 ans et issus des trois grandes régions linguistiques de Suisse sont interrogés tous les deux ans par la Haute école zurichoise en sciences appliquées (ZHAW) sur leur utilisation des médias. Les thèmes de cette enquête représentative s’articulent autour de leurs activités de loisirs avec ou sans médias. Une analyse approfondie a été menée sur l’utilisation des smartphones, jeux vidéo et des réseaux sociaux. Pour la première fois, l’enquête révèle des tendances. Les graphiques et explications qui suivent offrent un premier aperçu du rapport détaillé des résultats qui paraîtra début 2015.
Keywords: adolescence; jeunesse; lecture numérique; technologie mobile

Reading, Writing, and Literacy 2.0 Teaching with Online Texts, Tools, and Resources, K-8 - Denise Johnson (International Reading Association, Newark, DE, 2014)
In today's high-stakes testing environment, integrating technology into the curriculum is often seen as something ''extra'' or for use with a few special projects. With the growth in Internet use by even the youngest children, educators urgently need a practical introduction to online literacy and reading comprehension. Reading, Writing, and Literacy 2.0 offers that and more by providing tools and teaching strategies for incorporating online reading and writing into classroom learning, as well as a host of web resources that teachers can draw on to make this happen. All this without endless hours of searching! Denise Johnson's book connects to the Common Core State Standards and is organized around the Technological Literacy Assessment of the National Assessment of Education Progress (NAEP), which focuses on three areas that characterize a technologically literate person: knowledge, capabilities, and critical thinking and decision making. This resource provides everything reading teachers need to begin using technology to deepen and enrich literacy learning for all students. In addition, the author maintains a companion blog to update and add helpful teaching links.
Keywords: compréhension; éducation; jeunesse; lecture numérique; littératie numérique

Digging Deeper : Online Reading Comprehension and Collaborative Inquiry. Providence - Julie Coiro; Michelle Schira Hagerman (RI : Summer Institute on Digital Literacy, 2013)
Keywords: compétences; jeunesse; lecture numérique

Enhanced eBooks and multimodal publishing: spitting games and making claims with multimodal data - Hammond, Simon P. (Qualitative Research, 2013)
The ubiquity of digital technologies has led to an increase in the use of video-based research, the development of multimodal methodologies and the analysis of this material across a range of perspectives. The possibilities that multimodal research approaches exploring the interplay of image, talk and movement create, however, are reliant upon a less-than-multimodal way of publishing such work. This article considers how ‘enhanced eBooks’, which can incorporate text, audio and audiovisual material as one complete document, may allow for the inclusion of multimodal data to enrich qualitative research, providing a model for how this can be accomplished. To do this, multimodal materials from a study in which vulnerable adolescents revisited places of personal importance and recorded the narratives such visits elicited via camcorder are examined. The transcript, audiovisual clips and analysis presented provide an insight into the possibilities that multimodal publications herald, with discussions reflecting the challenges and possibilities it generates.   Keywords digital technologies, discourse analysis, enhanced eBooks, multimodal methods, participatory video, qualitative methods, qualitative research, transcription, visual ethics, young people
Keywords: analyse du discours; jeunesse; méthodologie; multimodalité

A framework for sustainable mobile learning in schools - Ng, Wan; Nicholas, Howard (British Journal of Educational Technology, 2013)
While there are studies that have looked at the implementation of mobile learning in educational institutions, particularly the identification of issues encountered, few studies have explored holistically the elements that sustain mobile learning. This study dissects the findings of a longitudinal study of a secondary school adopting a personal digital assistant programme and proposes a person-centred sustainable model for mobile learning.
Keywords: culture numérique; enseignement; jeunesse; technologie mobile

L'adoption du livre numérique, au Canada, chez les parents et les enfants - Solym, Clément (AL-Actualitté, les univers du livre, 2013)
L'organisme canadien BookNet, à but non lucratif, présente les résultats d'une étude portant sur les lecteurs adolescents, montrant que si plus du quart d'entre eux lit en numérique, ce chiffre va augmenter. Dans les foyers canadiens, on retrouve en effet une demi-douzaine d'appareils que les ados utilisent quasiment tous - et parfois pour lire. Même les familles qui ne lisent pas d'ebooks estiment qu'elles s'y mettront sous peu.
Keywords: jeunesse; lecture numérique

Les technologies mobiles en classe : Encadrer leur utilisation pour soutenir l’apprentissage des étudiants - Blondin, Jean-Pierre (Commission des études de l’Université de Montréal, 2013)
Sommaire des pratiques actuelles dans les grandes universités canadiennes en matière d’utilisation des technologies mobiles en classe tout en intégrant les résultats de recherches sur le sujet.
Keywords: enseignement; jeunesse

New school art styles : The project of art education - Gude, Olivia (Art Education, the Journal of the National Art Education Association, 2013)
Propositions de nouveaux axes concernant l'enseignement en art, avec des focus et des priorisations différentes dans la mise en place du curriculum (par projets, avec un focus sur les processus artistiques, la transmission d'outils de construction de sens, et contextualisation des expériences, et priorisation sur l'actualité des médiums). Exploration de nouveaux modes d'apprentissages et d'enseignements, notamment collaboratifs.
Keywords: création; enseignement; jeunesse

What is new about the new literacies of online reading comprehension - Donald J. Leu; Lisa Zawilinski; Jill Castek; Manju Banerjee; Brian C. Housand; Yingjie Liu; Maureen O’Neil (Secondary School Literacy: What Research Reveals for Classroom Practice, 2013)
Change defines literacy (Coiro, 2003; Hartman, 2000; Leu, 2000; Rosenblatt, 1938). Our lives change in fundamental ways as we become literate, expanding access to information, communication, and action (Freire, 1972, 1985; LeVine, LeVine, & Schnell, 2001). Because understanding change is at the core of what we do, it is ironic that our research community has largely ignored the extensive changes to literacy taking place in a digital, networked, multimodal, and multitasking world of information and communication. The nature of literacy is undergoing profound change, and we have little research or solid theory to inform our understanding of the consequences for classroom practice (Reinking, 1998).
Keywords: éducation; jeunesse; lecture numérique; multimodalité; pédagogie

Digital fluency : towards young people’s critical use of the Internet - Miller, C; Bartlett, J (Journal of Information Literacy, 2012)
The rise of the internet as the greatest source of information for people living in the UK today poses an acute challenge to the information literacy (IL) community. The amount and type of material available a mouse click away is both liberating and asphyxiating. There are more e-books, trustworthy journalism, niche expertise and accurate facts at our fingertips than ever before, but also mistakes, half-truths, propaganda and misinformation. This article presents research on how well young people are being equipped to meet the challenge of sorting good information from bad. It reviews current literature on the subject, and presents a new poll of over 500 teachers. With analysis supplemented by additional correspondence from librarians and other IL professionals, it argues that there is strong evidence that the web is fundamental to pupils’ learning and lives, but that many are not careful, discerning users of the internet. They are unable to find the information they are looking for, or they trust the first thing they see. This makes them vulnerable to the pitfalls of ignorance, falsehoods, cons and scams. The article proposes the appropriate response to be to embed ‘digital fluency’ – a tripartite concept constituting critical thinking, net savviness and diversity – at the heart of learning, in order to create a pedagogical framework fit for the information consumption habits of the digital age. It should be noted that both authors recognise the importance of non-teaching information literacy professionals in these debates. They recognise that the poll’s focus on teachers was too narrow, and have endeavoured, subsequent to the poll, to consult more widely in their research. Keywords information literacy; digital literacy; secondary education, primary education; children; teaching
Keywords: école primaire; école secondaire; enseignement; Information literacy model; jeunesse; littératie numérique

Jeunesses 2.0. : Les pratiques relationnelles au cœur des médias sociaux. - Endrizzi, Laure (Dossier d'actualité veille et analyses, 2012)
Après une première partie introductive sur la place des médias sociaux dans l'environnement culturel, l'auteur cherche à savoir si les pratiques numériques des jeunes font communauté, c'est-à-dire si elles sont ou non le fait d'une génération de natifs. Elle s'intéresse ensuite aux usages communicationnels qui nourrissent le quotidien numérique des jeunes et aux nouvelles sociabilités qui s'y développent Elle examine enfin les dynamiques identitaires à l'oeuvre et en particulier comment ils redéfinissent les frontières entre espace public et espace privé et comment ils cherchent à faire la preuve de leur valeur.
Keywords: communautés; culture numérique; jeunesse; médias sociaux

Les métamorphoses de l'oeuvre et de l'écriture à l'heure du numérique : Vers une renouveau des humanités? - Pham Ba, Christophe; Bonnin, Laurence; Conductier, Nathalie; Barbirati, Delphine; Boublil, Yaël; Barrier, Sylvie; Sospedra-Tessier, Christèle; Delord, Robert; Khaldi, Dominique; Sadler, Jérôme; Degoulet, Miguel; Bach, Ariane; et al. (Rendez-vous des lettres, 2012)
Présentation et propositions d'activités intégrant des outils numériques dans le cadre de l'enseignement des lettres.
Keywords: enseignement; jeunesse

Literacy artifacts and the semiotic landscape of a spanish secondary school. - Poveda, David (Reading Research QuarterlyReading Research Quarterly, 2012)
In this article, author examines literacy artifacts placed by students in different locations of a state-run secondary school in the city of Madird. The analysis draws from concepts developed in semiotics, linguistics anthropology, literacy studies, and social geography.
Keywords: enseignement; jeunesse; linguistique; literacy; sémiotique

Literacy, media and multimodality : A critical response. - Bazalgette, Cary; Buckingham, David (LiteracyLiteracy, 2012)
In recent years, literacy educators have increasingly recognised the importance of addressing a broader range of texts in the classroom. This article raises some critical concerns about a particular approach to this issue that has been widely promoted in recent years – the concept of ‘multimodality’. Multimodality theory offers a broadly semiotic approach to analysing a range of communicative forms. It has been widely taken up by literacy educators, initially at an academic level, and has begun to find its way into policy documents, teacher education and professional development and classroom practice. This article presents some criticisms, both of the theory itself and of the ways in which it has been taken up within the wider context of curriculum change. It argues that, in its popular usage, multimodality theory is being appropriated in a way that merely reinforces a long-standing distinction between print and ‘non-print’texts. This contributes in particular to a continuing neglect of the specificity of moving image media – media that are central to the learning and everyday life experiences of young children. Drawing on recent classroom-based research, the article concludes by offering some brief indications of an alternative approach to these issues.
Keywords: critical literacy; digital literacy/ies; enseignement; jeunesse; média; multimodalité; new literacies; popular culture

Caractériser les pratiques informationnelles des jeunes : Les problèmes laissés ouverts par les deux conceptions « natifs » et « naïfs » numériques - Nicole Boubée ((Communication Rencontres Savoirs CDI, Nouveaux supports, nouveaux espaces, nouvelles médiations), 2011)
La question des pratiques informationnelles numériques des jeunes est investie par deux conceptions que nous désignons1, à l’aide d’une allitération, par « natifs numériques » et « naïfs numériques ». Elles s’opposent radicalement sur l’existence des capacités des plus jeunes à faire usage des technologies numériques, et particulièrement pour rechercher de l’information. Bien que ces deux conceptions ne soient pas de même nature, l’une jouant essentiellement sur la force des mots et l’autre s’appuyant sur la preuve empirique, dans cette communication, je propose une analyse critique des deux approches visant à mettre en lumière les problèmes que celles-ci laissent respectivement ouverts. Pour les besoins de cette discussion, je procède en deux temps, correspondant à la critique successive des deux conceptions. J’aborde en premier la question de l’existence d’une génération différente des générations précédentes dans ses usages des technologies numériques, existence soutenue par la conception « natifs numériques ». Plusieurs objections empiriques écartent sans ambiguïté l’idée d’un renouvellement générationnel rapide et sans précédent. Il n’en reste pas moins que l’approche « natifs » s’inscrit dans un questionnement passionnant, celui des effets des technologies de diffusion massive de l’information, autrement dit des médias, sur les capacités cognitives. Le deuxième temps est consacré à la présentation des caractéristiques des pratiques informationnelles juvéniles identifiées par la conception « naïfs numériques ». Bien des traits auraient pu être présentés tant les travaux, quasi-exclusivement menés dans le domaine anglo-saxon, abondent. J’en retiens quatre qui éclairent les tendances de fond de l’activité informationnelle juvénile et les changements en cours. Comment les analyser ? Peut-on s’en tenir à l’explication par les connaissances et capacités informationnelles fortement limitées comme s’y emploie depuis plus de deux décennies la conception « naïfs numériques », approche scientifique dominante dans ce domaine ?
Keywords: jeunesse; lecture numérique; recherche d'information

Emerging technologies, ubiquitous learning, and educational transformation - Dede, Chris (Towards ubiquitous learning, 2011)
Emerging technologies are enabling ubiquitous learning. This can empower a structural change away from classrooms as the primary place of learning, the school day as the primary educational time, and the teacher as the primary source of information. Mobile devices can allow teachers to link to tutors, coaches, and mentors outside of school in a seamless web of support for each student. The author is conducting research on sophisticated analytics to mine rich datastreams collected on students’ devices, using each learner’s interactions to help in developing personalized educational experiences. We also are studying “augmented realities” that infuse virtual data and authentic, simulated experiences into real world settings, facilitating transfer of learning from classrooms to life. However, to realize the full power of ubiquitous learning for educational transformation, educators must overcome numerous challenges related to devices and infrastructure, safety and privacy, digital assets and assessments, and human capital.
Keywords: apprentissage; enseignement; jeunesse; réalité augmentée

L'activité informationnelle juvénile - Boubée, Nicole; Tricot, André (Hermès Lavoisier, 2011)
Cerner et comprendre les moyens qu’utilisent les jeunes et les élèves du secondaire dans leur recherche d’information suppose de prendre en compte les caractéristiques générales et spécifiques de celle-ci. Afin de déterminer si la comparaison habituelle entre experts et novices est toujours valable, les auteurs renouvellent le dispositif d’observation et s’appuient sur une méthodologie couplant observations directes et entretiens d’autoconfrontation. Les résultats exposés et analysés portent sur quatre points : les stratégies informationnelles, les critères de pertinence en jeu dans l’évaluation des documents, les fonctions particulières de l’image et le rôle des copier-coller. Les implications pédagogiques et les perspectives en lien avec l’évolution des environnements documentaires sont également abordées. Texte en lien : https://questionsdecommunication.revues.org/661
Keywords: élève du secondaire; évaluation; jeunesse; lecture numérique; pédagogie; recherche documentaire

Les « C » en tant que citoyens - Roy, Réjean (CEFRIO, 2011)
Enquête et analyse des impacts des nouvelles technologies sur les perceptions de leur monde par les jeunes, et sur leur engagement social.
Keywords: culture numérique; internet; jeunesse; univers social

Rapport sur la participation aux activités artistiques et de lecture des enfants en dehors de l'école en 2008 - Hill, Kelly (Regards statistiques sur les arts, 2011)
Récolte de données sur la participation aux activités artistiques et de lecture des enfants en dehors de l'école (3 à 7 ans).
Keywords: création; jeunesse

Seeking the green basilisk lizard : Acquiring digital literacy practices in the home - Christina Davidson (Journal of Early Childhood Literacy, 2011)
Research confirms that young children engage in digital literacy practices in the home. While there is an emerging body of work that documents the diversity of these practices, there is little research that examines their acquisition in situ. This article uses conversation analysis to describe and explicate the social accomplishment of a number of activities that led to and constituted a young child’s Google search to find information about a lizard. Discussion of the child’s activities considers the local and situated use of technology, including how the child and adult jointly obtained the information needed by the child to read and write texts related to the search. The article establishes ways that social interaction contributes to young children’s acquisition and use of digital literacy practices, including when learning about print and about techology itself.   Keywords : conversation analysis, digital literacy practices, home, social accomplishment, young children
Keywords: jeunesse; lecture numérique

TIC et rapport à la lecture. Étude de la réception d'une bibliothèque interactive auprès d'un public d'enfant - SOPHIE ODENA; JÉRÔME QUARTANA (Bulletin des bibliothèques de France, 2011)
Depuis les années 1980, la tendance est à la baisse de l’intensité de la lecture et chaque nouvelle génération arrive à l’âge adulte avec un niveau d’engagement dans cette pratique culturelle inférieur à celui de la génération précédente [2]. La lecture est de moins en moins souvent inscrite dans le quotidien des enfants et des adolescents qui lui préfèrent d’autres pratiques culturelles [4]. Cependant, cet éloignement de la lecture ne se fait pas de façon homogène parmi les nouvelles générations et les enfants de parents forts lecteurs (souvent des cadres) sont eux-mêmes plus enclins à lire que les enfants de parents non-lecteurs (plus souvent des ouvriers).
Keywords: jeunesse; lecture numérique; pratiques culturelles

Film as identity exploration : A multimodal analysis of youth produced films - Rosenfeld Halverson, Erica (Teachers College RecordTeachers College Record, 2010)
Construction d'un cadre analytique permettant la compréhension des liens entre les films faits par des jeunes et la création et la représentation de l'identité, par la mise en lien de films et de cadres d'analyse sémiotique existants. Les éléments filmiques et cinématiques sont pris en considération (format multimodal).
Keywords: identité; jeunesse; multimodalité

Hanging out, messing around and geeking out : kid living and learning with new media - Ito, Mizuko; Baumer, Sonia; Bittanti, Matteo; Boyd, Danah; Cody, Rachel; Herr-Stephenson, Becky; Horst, Heather; Lange, Patricia; Mahendran, Dilan; Martinez, Katynka; Pascoe, C.J.; Robinson, Laura; et al. (The John D. and Catherine T. MacArthur Foundation Series on Digital Media and Learning, 2010)
Conventional wisdom about young people’s use of digital technology often equates generational identity with technology identity: today’s teens seem constantly plugged in to video games, social networking sites, and text messaging. Yet there is little actual research that investigates the intricate dynamics of youths’ social and recreational use of digital media. Hanging Out, Messing Around, and Geeking Out fills this gap, reporting on an ambitious three-year ethnographic investigation into how young people are living and learning with new media in varied settings—at home, in after-school programs, and in online spaces. Integrating twenty-three case studies—which include Harry Potter podcasting, video-game playing, music sharing, and online romantic breakups—in a unique collaborative authorship style, Hanging Out, Messing Around, and Geeking Out is distinctive for its combination of in-depth description of specific group dynamics with conceptual analysis.
Keywords: jeunesse

L'incidence du numérique sur les pratiques culturelles des jeunes québécois - Jutras, Dominique (IVèmes journées internationales des observatoires de la culture, 2010)
Cette intervention vise à brosser le portrait non exhaustif de l'appropriation et des usages que font les jeunes des biens et services culturels numériques, à travers des données chiffrées recouvrant les achats matériels, les statistiques de téléchargement de musique, les consommations internet, etc. (voir études pour données chiffrées).
Keywords: jeunesse; univers social

Media arts : Arts education for a digital age - Peppler, Kylie A. (Teachers College RecordTeachers College Record, 2010)
The researcher draws upon over three years of extensive field study at a Computer Clubhouse (media arts studio) in south Los Angeles where underprivileged youth ranging in age from eight to 18 have access to programming environments utilizing graphic, music, and video production software. Using a mixed-methods design including interviews with young artists at the Clubhouse, video footage of Clubhouse youth in the process of art making, and an archive of youth media art projects, the researcher documents what youth learn through media arts making in informal settings. She also describes the implications for leveraging learning in a media arts context for learning in other academic content areas.
Keywords: création; enseignement; jeunesse

Confronting the challenges of participatory cultures (media education for the 21st century) - Jenkins, Henry; Purushotma, Ravi; Weigel, Margaret; Clinton, Katie; Robison, Alice (The John D. and Catherine T. MacArthur Foundation Reports on Digital Media and Learning, 2009)
Cultures participatives (engagement, partage, connection sociale) et leurs impacts sur l'acquisition d'expertises et de connaissances. Nécessité de l'encadrement pédagogique de ces cultures, afin de doter les jeunes d'outils de compréhension et d'acquisition dans de nouvelles formes médiatiques. Modes, outils, techniques et modes d'enseignement.
Keywords: enseignement; jeunesse; participation

The digital native : myth and reality - Neil Selwyn (New information perspective, 2009)
Purpose – The purpose of this paper is to develop and promote a realistic understanding of young people and digital technology with a view to supporting information professionals in playing useful and meaningful roles in supporting current generations of young people. In particular the paper aims to offer a critical perspective on popular and political understandings of young people and digital technologies – characterised by notions of “digital natives”, the “net generation” and other commonsense portrayals of expert young technology users. The paper seeks to consider the accuracy of such descriptions in reflecting young people’s actual uses of digital technology and digital information. Design/methodology/approach – The paper provides a comprehensive review of the recent published literatures on young people and digital technology in information sciences, education studies and media/communication studies. Findings – The findings show that young people’s engagements with digital technologies are varied and often unspectacular – in stark contrast to popular portrayals of the digital native. As such, the paper highlights a misplaced technological and biological determinism that underpins current portrayals of children, young people and digital technology. Originality/value – The paper challenges the popular assumption that current generations of children and young people are innate, talented users of digital technologies. Having presented a more realistic basis for approaching generational differences in technology use, the paper explores the functions and roles that information professionals can be expected to play in supporting young people in the digital age.   Keywords Children (age groups), Youth, Internet, Digital communication systems
Keywords: jeunesse; lecture numérique

La balado : Une façon d'apprendre appréciée des jeunes - Dubuc, Richard (Clic, Bulletin collégial des technologies de l'information et des communications, 2009)
Conférence d'un professeur de CEGEP sur son expérience d'insertion de dispositifs de balado-diffusion en classe.
Keywords: baladodiffusion; enseignement; jeunesse

La Participation médiatique selon H. Jenkins (note critique) - François, Sébastien (Terrains et travaux, ENS CachanTerrains et travaux, ENS Cachan, 2009)
Étude de l'élaboration et de l'impact des théories de Jenkins sur la "Culture convergente", liées aux activités amateures sur internet et dérivées des mass-medias, du statut de ces pratiques, et de leurs modes de développement. Cultures participatives et amateurs.
Keywords: internet; jeunesse; participation

Les 12-24 ans : utilisateurs extrêmes d’Internet et des TI - Roy, Réjean (CEFRIO, 2009)
De nombreux chercheurs croient que l’utilisation que les jeunes font des technologies de l’infor- mation (TI) a un impact marqué sur les étudiants, les consommateurs, les travailleurs et les citoyens qu’ils sont ou deviendront, un impact qui forcera les organisations de tous les secteurs à apporter des transformations majeures à leurs pratiques. Que sait-on de cette utilisation? C’est pour répondre à cette question, qui précède toutes les autres, que le CEFRIO amené l’enquête Génération C.
Keywords: jeunesse

Pratiques culturelles chez les jeunes et institutions de transmission : Un choc des cultures? - Octobre, Sylvie (Culture Prospective, par DEPS, 2009)
Avec la révolution numérique, les usages culturels évoluent, particulièrement dans les générations des digital natives, jeunes familiers des technologies de l’information et de la communication. Pour autant, les nouveaux usages culturels des jeunes (10-24 ans) ne sont pas exclusifs : les pratiques artistiques amateurs, la fréquentation des équipements culturels et la consommation médiatique se maintiennent auprès des jeunes générations où l’usage de l’internet apparaît lié à un intérêt plus global pour la culture et l’information. Le genre, l’âge et l’appartenance à une catégorie socioprofessionnelle demeurent des variables significatives. C’est du côté des instances de transmission – la famille, l’école et les institutions culturelles – que les évolutions sont les plus notables : celles-ci interrogent les instances de transmission (famille, école, équipements culturels) à repenser leurs modes d’action, qu’il s’agisse de transmission familiale, du lien entre culture et savoir ou encore de médiation.
Keywords: enseignement; jeunesse

Translocal style communities : Hip-hop youth as cultural theorists of style, language and globalization - Samy Alim, H. (Pragmatics, 2009)
This article addresses issues that lie at the intersection of debates about language, Hip Hop Culture, and globalization. Critically synthesizing a wide range of recent work on Hip Hop and foregrounding issues of youth agency as evidenced by Hip Hop youths metalinguistic theorizing, the article presents an empirical account of youth as cultural theorists. Hip Hop youth are both participants and theorists of their participation in the many translocal style communities that constitute the Global Hip Hop Nation. Highlighting youth agency, the article demonstrates that youth are engaging in the agentive act of theorizing the changes in the contemporary world as they attempt to locate themselves at the intersection of the local and the global. The article concludes by calling for a linguistic anthropology of globalization characterized by ethnographic explorations of and a theoretical focus on popular culture, music, and mass-mediated language as central to an anthropological understanding of linguistic processes in a global era.
Keywords: création; hip hop cultures; jeunesse; linguistique

Connecting informal and formal learning experiences in the age of participatory media - Bull, Glen; Thompson, Ann; Searson, Mike; Garofalo, Joe; Park, John; TYoung, Carl; Lee, John (Contemporary issues in technology and teacher educationContemporary issues in technology and teacher education, 2008)
The renaissance stimulated by the World Wide Web is generating multiple formats and channels of communication and creativity. The Pew Internet and American Life project reports that the majority of all teens are now engaged in active creation of online content. The rise of social media reflects new opportunities and outlets for creativity. Increased youth engagement through these activities represents a repurposing of what Clay Shirky terms a cognitive surplus . Shirky believes that a movement from passive activities such as watching television to more active and creative pursuits is emerging as a use of the cognitive surplus in the Web 2.0 era. Collaborative projects such as Wikipedia demonstrate that a previously unexploited collective intelligence can be tapped when the right conditions are established. This study is about new projects and processes with new media.
Keywords: internet; jeunesse; médias sociaux

Digital literacies : tracing the implications for learners and learning - Livingstone, Sonia (The educational and social impact of new technologies on young people in Britain, 2008)
Approche pluridisciplinaire des questions du contexte et des impacts de l'utilisation des nouvelles technologies de communication par les jeunes. Lien entre la littératie digitale et le capital social, et impacts sur le développement de compétences de l'utilisation de nouveaux moyens de communication, posant par voie de conséquence la question de de l'injustice sociale subi par les élèves n'ayant pas accès à ces nouveaux modes. Analyse de l'expérience de nouvelles technologies en classe d'élèves du primaire et du secondaire et de leurs propres réflexions sur leur littératie. Réflexions sur la mise en place d'une culture particpative autogérée. Analyse des cadres de référence de la communication, de ses différentes formes et contraintes.
Keywords: enseignement; jeunesse

Internet literacy : Young people's negotiation of new online opportunities - Livingstone, Sonia (Digital youth, innovation, and the unexpected, 2008)
Proposition d'un cadre d'analyse des usages d'Internet et des compétences nécessaires associées, à travers le spectre de la littératie, permettant de déterminer les compétences développées, associant à la fois compétences individuelles et pratiques sociales. Analyse des nouveaux modes de réception de l'information générés par Internet.
Keywords: internet; jeunesse

Living and learning with new media : Summary of findings from the digital youth project - Ito, Mizuko; Horst, Heather; Bittanti, Matteo; Boyd, Danah; Herr-Stephenson, Becky; Lange, Patricia; Pascoe, C.J.; Robinson, Laura; Baumer, Sonia; Cody, Rachel; Mahendran, Dilan; Martinez, Katynka; et al. (The John D. and Catherine T. MacArthur Foundation Series on Digital Media and Learning, 2008)
The researchers explain why youth find activities such as online games, social network, etc., compelling and important. The digital world is creating new opportunities for youth to grapple with social norms, explore interests, develop technical skills, and experiment with new forms of self-expression. These activities have captured teens attention because they provide avenues for extending social worlds, self-directed learning, and independence.
Keywords: jeunesse; jeux vidéo

Que font les adolescents de leurs journées? - Haley, Kirstin (Enquête sociale générale, 2008)
Étude et enquêtes sur les pratiques quotidiennes des adolescents en dehors de leurs temps scolaires.
Keywords: jeunesse

Teaching literacy in the new media age through the arts - Walsh, Christopher (Literacy Learning : The middle years, a journal of the Australian literacy educators association, 2008)
Acquisition de compétences et connaissances par les jeunes, via des formes culturelles et sociales multimodales, souvent supportées par des nouvelles technologies. Reconnaissance de la créativité inhérente dans les curricula, et utilisation de techniques culturelles dans les enseignements.
Keywords: enseignement; jeunesse

Worlds have collided and modes have merged : Classroom evidence of changed literacy practices - Walsh, Maureen (LiteracyLiteracy, 2008)
Debates continue in public and in educational policy forums about the ‘basics’ of literacy while many have not recognised that these basics may never be the same again. Rapid changes in digital communication provide facilities for reading and writing to be combined with various and often quite complex aspects of music, photography and film. At the same time, educational policy and national testing requirements are still principally focused on the reading and writing of print-based texts. This paper examines evidence from classroom research to analyse the nature of multimodal literacy, the literacy that is needed in contemporary times for reading, viewing, responding to and producing multimodal and digital texts. Examples of students' engagement in multimodal literacy are presented to demonstrate how classroom literacy practices can incorporate the practices of talking, listening, reading and writing together with processing the modes of written text, image, sound and movement in print and digital texts.
Keywords: écriture et lecture numériques; enseignement; jeunesse; lecture; littératie; multimodalité

Assessing aesthetic relevance: Children's book selection in a digital library - Kara Reuter (Journal of the American Society for Information Science and Technology, 2007)
Recreational reading among young people is reportedly on the decline in the United States. Some researchers have suggested that supporting children’s strategies for book selection is crucial to encouraging children to engage with books, indicating that improving these strategies might increase the amount of reading they do. In response, this study explores how elementary-school children select books for recreational reading using a digital library. The work extends traditional models of relevance assessment with reader-response theory, employing the concept of “aesthetic relevance”: the potential of a document to provide a suitable reading experience. Individuals define aesthetic relevance in personal terms and apply it as they assess documents, much as they do in traditional relevance assessment. This study identified a total of 46 factors organized along seven dimensions that influence children’s assessment of the aesthetic relevance of books during selection. The analysis yielded differences in the prevalence of the aestheticrelevance factors that children mention at various stages of book selection. In addition, the children exhibited differences by age and subtle differences by gender in the frequency of mention of various aesthetic-relevance factors. Recommendations drawn from the findings are offered to improve systems design and literacy education in order to enhance children’s access to books and to promote recreational reading.
Keywords: évaluation; genre; jeunesse; lecture numérique; recreational reading

Children's interaction with cross-cultural and multilingual digital libraries: I. Understanding interface design representations - Dania Bilal; Imad Bachir (Information Processing and Management, 2007)
This paper reports the results of a study that examined Arabic-speaking children’s interaction with the International Children’s Digital Library (ICDL). Assessment of the ICDL to Arabic-speaking children as a culturally diverse group was grounded in “representations” and “meaning” rather than in internationalization and localization. The utility of the ICDL navigation controls was judged based on the extent it supported children’s navigation. Most of the ICDL representations and their meanings were found to be highly appropriate for older children but inappropriate for younger ones. The design of the ICDL navigation controls was supportive of children’s navigation. Recommendations for assessing the cross-cultural usability of the ICDL are made and suggestions for system design improvements are provided.
Keywords: ergonomie des interfaces; évaluation; jeunesse; lecture numérique

From supergoo to scratch : Exploring creative digital media production in informal learning - Peppler, Kylie A.; Kafai, Yasmin B. (Learning, Media & Technology, 2007)
Based on work in media studies, new literacy studies, applied linguistics, the arts and empirical research on the experiences of urban youths' informal media arts practices, the authors articulates a new vision for media education in the digital age that encompasses new genre, convergence, media mixes and participation.
Keywords: enseignement; jeunesse; literacy; média

Gradations in digital inclusion : children, young people and the digital divide - Livingstone, Sonia; Helsper, Ellen (New Media and Society, 2007)
Little academic and policy attention has addressed the ‘digital divide’ among children and young people. This article analyses findings from a national survey of UK 9-19 year olds that reveal inequalities by age, gender and socioeconomic status in relation to their quality of access to and use of the internet. Since both the extent of use and the reasons for low and non-use of the internet vary by age, a different explanation for the digital divide is required for children compared with adults. Looking beyond the idea of a binary divide, we propose instead a continuum of digital inclusion. Gradations in frequency of internet use (from non and low users through to weekly and daily users) are found to map onto a progression in the take-up of online opportunities among young people (from basic through moderate to broad and then all-round users), thus beginning to explain why differences in internet use matter, contributing to inclusion and exclusion. Demographic, use and expertise variables are all shown to play a role in accounting for variations in the breadth and depth of internet use.
Keywords: digital divide; digital inclusion; internet; jeunesse

How young people view their lives, futures and politics : A portrait of Generation Next - Kohut, Andrew; Parker, Kim; Keeter, Scott; Doherty, Carroll; Dimock, Michael (Pew Research Center for the People & the Press, 2007)
Ce rapport vise à dresser le portrait de la Génération Next (18 - 25), la génération ayant grandi avec ordinateurs personnels, téléphones cellulaires et internet : usages sociaux, création, rapport aux technologies, vues politiques, ambitions, sont autant des points qui sont abordés. Il est notamment intéressant de noter leur propension à l'interconnexion et l'auto-singularisation.
Keywords: jeunesse

“Indnpride” : Online spaces of transnational youth as sites of creative and sophisticated literacy and identity work - McGinnis, Theresa; Goodstein-Stolzenberg, Andrea; Coasta Saliani, Elisabeth (Linguistics and Education, Elsevier, 2007)
Transnational youth are increasingly engaged in online culture that not only transcends geographic distances and boundaries, but has also become an integral part of their identities and social realities. This article explores the significance of three transnational youth’s uses of digital literacies. Specifically, we discuss the ways these youth present particular identities, including transnational identities, through the hybrid textual practices of online communication sites.We suggest that these technological sites are important and dynamic representational spaces for youth to engage in transformative literacy practices and identity work.
Keywords: identité; jeunesse; littératie; transnationalisme

Console video games and global corporations : Creating a hybrid culture. - Consalvo, Mia (New Media and SocietyNew Media and Society, 2006)
This article argues that the contemporary console video game industry is a hybrid encompassing a mixture of Japanese and American businesses and (more importantly) cultures to a degree unseen in other media industries, especially in regard to US popular culture. The particularities of the video game industry and culture can be recognized in the transnational corporations that contribute to its formation and development; in the global audience for its products; and in the complex mixing of format, style and content within games. As an exemplar of this process, the Japanese game publisher Square Enix is the focus of this case study, as it has been successful in contributing to global culture as well as to the digital games industry through its glocal methods. That achievement by a non-Western corporation is indicative of the hybridization of the digital games industry, and it is examined here as one indicator of the complexities and challenges, as well as future potentials, of global media culture.
Keywords: enseignement; industries culturelles; jeunesse; jeux vidéo

Les adolescents branchés - Rigaud, Claude (Dossier de veille de l'Institut français de l'éducationDossier de veille de l'Institut Français de l'Éducation, 2006)
Cette étude vise à rassembler différentes données (chiffrées et analytiques) sur les cultures numériques des adolescents, et vise à dresser un portrait de leurs usages et des impacts de ces nouvelles pratiques sur les potentiels d'enseignements et les méthodes pédagogiques. L'article revient notamment sur les modifications apportées par la révolution numérique aux codes sociaux (intense socialisation, construction de communauté, socialité horizontale) et aux notions d'identité et de rapport au corps.
Keywords: culture numérique; jeunesse

Mobile culture : An ethnography of cellular phone uses in teenagers' everyday life - Caronia, Letizia (Convergence : The International Journal of Research into New Media Technologies, 2005)
Cet article retrace le contexte de déploiement et les résultats de recherche de deux études portant sur les usages des cellulaires par les adolescents, la première s'intéressant à la création identitaire par cette nouvelle manière de construire des communautés, et la seconde aux usages et cultures du mobile par les jeunes (par l'enregistrement de leurs conversations, notamment). L'analyse des données permet d'illustrer les notions de coopérations créatives caractéristiques des relations personnels / technologies. Ces études s'inscrivaient dans la continuité d'une première enquête concernant l'intégration des nouvelles technologies au sein de cellules familiales canadiennes, qui avait révélé le caractère particulièrement impactant de l'arrivée des téléphones cellulaires, qui venait redéfinir rôles et interactions sociales au sein des familles, et se faisait créateur d'identités individuelles et collectives.
Keywords: adolescence; jeunesse; technologie mobile

Les pratiques culturelles adolescentes : France, début du troisième millénaire - Hersent, Jean-François (Bulletin des bibliothèques de France, 2003)
Le modèle de l'expérimentation semble le mieux approprié pour rendre compte des pratiques culturelles des adolescents. Les jeunes tirent de la conformité aux normes du groupe des pairs reconnaissance et satisfaction, alors même qu'ils n'ont jamais une véritable autonomie normative et culturelle. À ce modèle, s'ajoutent plusieurs facteurs : d'une part, le recul de la culture consacrée, une certaine forme d'anti-intellectualisme, la valorisation de l'éclectisme, la montée de l'économie médiatico-publicitaire ; d'autre part, le fait que cette génération est la première à avoir connu dès l'enfance un paysage médiatique extrêmement diversifié ; et enfin, le triomphe de la télévision de l'intimité.
Keywords: jeunesse; pratiques culturelles

Strip mining for gold : Research and policy in educational technology-A response to « Fool’s gold » - DOUGLAS H. CLEMENTS; JULIE SARAMA (Educational Technology Review, 2003)
Several recent articles have addressed the issue of the translation and interpretation of education research for the purpose of affecting policy (e.g., Educational Researcher 29(6).) We respond to the publication of, and media attention to1, Fool’s gold: A critical look at computers in childhood (Cordes & Miller, 2000). This report delineates some important issues for discussion and includes several valid concerns. However, we believe it’s presentation of half-truths and misleading interpretations of theory and research under the guise of academic respectability not only presents an unfortunate one-sided picture of the issues and related empirical research, but, more generally, plays the U.S. media game to the detriment of research, intellectual discourse, and, ultimately, children. Misuse of technology by some and overzealous promotion by others are not valid reasons for misrepresenting the field or for speciously framing the computer as the lightning rod for a broad range of criticisms that we argue can be reasonably attributed to no single source. Such incomplete and dishonest reporting misdirects attention from the wider web of political and pedagogical concerns, trammels the progress of research and expert practice that can guide developmentally appropriate and beneficial use of computers, and does violence to the academic enterprise by reinforcing the cynical belief that research can also support either of polar opposite opinions. In this article, we hope to correct misconceptions about computers in education, but more so, to argue for a complete, balanced, consideration and reporting of research, especially when addressing policy implications.
Keywords: jeunesse; lecture numérique; recherche en éducation

Exploring identities through the Internet : Youth experiences online - Maczewski, Metchild (Child and Youth Care ForumChild and Youth Care Forum, 2002)
How do youth experience their online interactions? This article presents youth voices talking about their online experiences and how they perceive these interactions to have influenced their lives highlighting three themes: the notion of “wowness” experiences of freedom, power, and connectedness; and expanding notions of self and identities. It explores how parameters of the Internet (anonymity, interactivity, and connectivity) assist in enabling powerful relations and interactions that benefit some youth very positively. Virtual interactions and online spaces are seen as further sites of interaction in which youth can explore their identities and sense of themselves.
Keywords: identité; jeunesse

A model of young people's decision-making in using the Web - Denise Agosto (Information Science Research, 2002)
This article offers a theoretical model of the criteria young people use to evaluate websites. The model combines the concepts of personal preferences, object engagement characteristics, human processing constraints, and contextual constraints to predict a young person's evaluation decision. The qualitative methodology used to gather data for the development and testing of this model included website evaluation sessions and group interviews with 11 young female students. Data analysis took the form of iterative pattern coding using QSR NUD*IST Vivo qualitative data analysis software. Data analysis uncovered strong support for the theoretical and empirical models. Related implications for website designers are discussed, with an emphasis on the importance of enabling users to modify website design to satisfy their personal preferences. Related implications for librarians and teachers are also discussed, with an emphasis on the importance of teaching young people to become more critical users of the Web.
Keywords: écriture et lecture numériques; genre; jeunesse

Effective learning environments for young children using digital ressources : An Australian perspective - Downes, T.; Arthur, L.; Beecher, B. (Childhood Education Annual, 2001)
The use of digital resources in early childhood settings in Australia is a recent phenomenon. In 1999 Education.Au, a company funded by the various educational authorities in Australia, commissioned a study of the educational use of the Internet with children eight years and under. Data were collected through a literature review and discussions or interviews with all stakeholders in early childhood education: children, families, early childhood educators, school system representatives, academics, researchers, policy makers and advisers. This paper reports on the major outcome of the commissioned study: a pedagogical framework for the use of digital resources in early childhood settings. The framework includes a rationale and a description of the key elements of effective practice: quality resources, effective learning environments and appropriate teacher interactions.
Keywords: contexte d'apprentissage; contexte d'enseignement; éducation; jeunesse; lecture numérique; recherche

Les jeunes et internet (représentation, utilisation et appropriation) - Piette, Jacques; Pons, Christian-Marie; Giroux, Luc; Millerand, Florence (Ministère de la Culture et des Communications, Gouvernement du Québec, 2001)
Synthèse d'enquête internationale concernant les relations de perceptions, d'usages et d'appropriation qu'entretiennent les jeunes avec internet. Les données ont été récoltées par des questionnaires et entretiens, et s'intéressent plus particulièrement les interactions entre les jeunes et Internet selon les principaux contextes dans lesquelles se déploient leur activité informatique, soit la maison, l'école, chez des amis, des lieux publics, etc. Les points importants sont les suivants : malgré le contexte international, les résultats sont très similaires d'un pays à l'autre (si ce n'est le taux d'implantation); l'extrême positivité de la perception de l'internet par les jeunes; la modération de leurs propos quant à leurs usages d'internet et de ses impacts, notamment sur la supposée menace sur leur identité culturelle; leur perception d'internet comme une source de divertissement et de communication; la confiance que les jeunes ont en l'information qu'ils trouvent sur la toile, l'importante variation entre les pratiques, le caractère individuel mais non solitaire des usages;  et le conformisme qu'il peut créér dans les modes de consommation. L'étude permet aussi de dresser le portrait des modes d'appropriation d'internet par les jeunes.
Keywords: culture numérique; internet; jeunesse

Les modes de vie et les pratiques culturelles des jeunes, homogénéisation de la culture et individualisation des pratiques? - Gauthier, Madeleine; Boily, Claire; Duval, Luce (Loisir et société, 2001)
Des changements dans les modes de vie coïncident avec un accroissement du temps consacré par les jeunes aux pratiques culturelles. L’élévation du niveau de scolarité y serait-il pour quelque chose dans cet intérêt des jeunes adultes pour la lecture, la fréquentation des bibliothèques et des librairies et celle des musées d’art où, dans ce dernier cas, ils sont les champions ? Faut-il voir dans ces différentes manifestations une certaine homogénéisation entre les âges en ce qui concerne les activités culturelles dites « classiques » ? Par ailleurs la diminution de l’attrait pour certaines activités, en particulier celles qui sont figées dans un horaire, serait-elle la marque d’une individualisation de la pratique chez ces mêmes jeunes que certains iraient jusqu’à qualifier d’individualisme ? Il semble bien que l’engouement des jeunes pour la pratique en groupe n’ait pas changé ; ce qui a changé, ce sont les contraintes de temps associées à certaines pratiques (fidélité à certaines émissions de télévision, abonnement au théâtre, etc.) et qui indiquent un déplacement de la sociabilité vers d’autres formes, mais non sa régression.
Keywords: jeunesse

Technology and young children : A review of literature - Alexandra E. Appel; D Chloe O’Gara (Tech-KnowLogia, 2001)
Interest in using personal computer technology as an instructional medium with young children is growing around the world. Many parents, teachers, and even national governments2 are convinced that early interaction with technology stimulates learning and gives children a head start on success in the technological world of the future. This article reviews current research on developmental issues and the use of technology in learning environments for 4, 5 and 6-year-old preschool children. The reviewers are cognizant of the controversy revolving around whether the developmental needs of children are best met when technology is introduced into the learning environment. However, since that technology is now prevalent in the social contexts of many young children, tracking best practice guidelines for the introduction of technology into early learning environments is a necessity for early childhood development professionals and educators. The goal of this brief review is to inquire how current practices address developmentally appropriate learning, and to review guidance on how best to use computers with young children.
Keywords: apprentissage; écriture et lecture numériques; jeunesse

Children's use of the Yahooligans! Search engine. I. Cognitive, physical and affective behaviors on fact-based search tasks - Dania Bilal (Journal of the American Society for Information Science and Technology, 2000)
This study reports on the first part of a research project that investigated children's cognitive, affective, and physical behaviors as they use the Yahooligans! search engine to find information on a specific search task. Twenty-two seventh-grade science children from a middle school located in Knoxville, Tennessee participated in the project. Their cognitive and physical behaviors were captured using Lotus ScreenCam, a Windows-based software package that captures and replays activities recorded in Web browsers, such as Netscape. Their affective states were captured via a one-on-one exit interview, A new measure called "Web Traversal Measure" was developed to measure children's "weighted" traversal effectiveness and efficiency scores, as well as their quality moves in Yahooligans! Children's prior experience in using the Internet/Web and their knowledge of the Yahooligans! interface were gathered via a questionnaire. The findings provided insights into children's behaviors and success, as their weighted traversal effectiveness and efficiency scores, as well as quality moves. Implications for user training and system design are discussed.
Keywords: cognition; jeunesse; lecture numérique

Children’s relevance criteria and information-seeking on electronic resources - Hirsh, S. G. (Journal of the American Society for Information Science, 1999)
This study explores the relevance criteria and search strategies elementary school children applied when searching for information related to a class assignment in a school library setting. Students were interviewed on two occasions at different stages of the research process; field observations involved students thinking aloud to explain their search processes and shadowing as students moved around the school library. Students performed searches on an on-line catalog, an electronic encyclopedia, an electronic magazine index, and the World Wide Web. Results are presented for children selecting the topic, conducting the search, examining the results, and extracting relevant results. A total of 254 mentions of relevance criteria were identified, including 197 references to textual relevance criteria that were coded into nine categories and 57 references to graphical relevance criteria that were coded into five categories. Students exhibited little concern for the authority of the textual and graphical information they found, based the majority of their relevance decisions for textual material on topicality, and identified information they found interesting. Students devoted a large portion of their research time to finding pictures. Understanding the ways that children use electronic resources and the relevance criteria they apply has implications for information literacy training and for systems design.
Keywords: jeunesse; lecture numérique; recherche d'information

Developmentally Appropriate Practice in Early Childhood Programs Serving Children from Birth through Age 8 - Auteur anonyme (NAEYC, 1996)
The purpose of this position statement is to promote excellence in early childhood education by providing a framework for best practice. Grounded both in the research on child development and learning and in the knowledge base regarding educational effectiveness, the framework outlines practice that promotes young children’s optimal learning and development. Since its first adoption in 1986, this framework has been known as developmentally appropriate practice. The profession’s responsibility to promote quality in the care and education of young children compels us to revisit regularly the validity and currency of our core knowledge and positions, such as this one on issues of practice. Does the position need modification in light of a changed context? Is there new knowledge to inform the statement? Are there aspects of the existing statement that have given rise to misunderstandings and misconceptions that need correcting? Over the several years spent in developing this revision, NAEYC invited the comment of early childhood educators with experience and expertise from infancy to the primary grades, including Developmentally Appropriate Practice in Early Childhood Programs Serving Children from Birth through Age 8 Note: Throughout this statement, the terms teacher, practitioner, and educator are variously used to refer to those working in the early childhood field. The word teacher is always intended to refer to any adult responsible for the direct care and education of a group of children in any early childhood setting. Included are not only classroom teachers but also infant/toddler caregivers, family child care providers, and specialists in other disciplines who fulfill the role of teacher. In more instances, the term practitioners is intended to also include a program’s administrators. Educators is intended to also include college and university faculty and other teacher trainers. Adopted 2009 Position Statement a late 2006 convening of respected leaders in the field. The result of this broad gathering of views is this updated position statement, which addresses the current context and the relevant knowledge base for developmentally appropriate practice and seeks to convey the nature of such practice clearly and usefully. This statement is intended to complement NAEYC’s other position statements on practice, which include Early Learning Standards and Early Childhood Curriculum, Assessment, and Program Evaluation, as well as the Code of Ethical Conduct and NAEYC Early Childhood Program Standards and Accreditation Criteria.
Keywords: apprentissage; éducation; jeunesse